Training Volume, Not Frequency, Indicative of Maximal Strength Adaptations to Resistance Training. Issue 5 (May 2018) - Colquhoun, Ryan J.; Gai, Christopher M.; Aguilar, Danielle; Bove, Daniel; Dolan, Jeffrey; Vargas, Andres; Couvillion, Kaylee; Jenkins, Nathaniel D.M.; Campbell, Bill I.
Abstract : Abstract: Colquhoun, RJ, Gai, CM, Aguilar, D, Bove, D, Dolan, J, Vargas, A, Couvillion, K, Jenkins, NDM, and Campbell, BI. Training volume, not frequency, indicative of maximal strength adaptations to resistance training. J Strength Cond Res 32(5): 1207–1213, 2018—To compare the effects of a high versus a moderate training frequency on maximal strength and body composition. Twenty-eight young, healthy resistance-trained men were randomly assigned to either: 3× per week (3×; n = 16) or 6× per week (6×; n = 12). Dependent variables (DVs) assessed at baseline and after the 6-week training intervention included: squat 1 repetition maximum (SQ1RM), bench press 1RM (BP1RM), deadlift 1RM (DL1RM), powerlifting total (PLT), Wilk's coefficient (WC), fat-free mass (FFM), and fat mass. Data for each DV were analyzed using a 2 × 2 between-within factorial repeated-measures analysis of variance. There was a main effect for time ( p < 0.001) for SQ1RM (3×: +16.8 kg; 6×: +16.7 kg), BP1RM (3×: +7.8 kg; 6×: +8.8 kg), DL1RM (3×: +19 kg; 6×: +21 kg), PLT (3×: +43.6 kg; 6×: +46.5 kg), WC (3×: +27; 6×: +27.1), and FFM (3×: +1.7 kg; 6×: +2.6 kg). There were no group × time interactions or main effects for group. The primary finding was that 6 weeks of resistance training led to significant increases in maximal strength and FFM. In addition, it seems that increased training frequency does not lead to additional strength improvements when volume and intensity are equated. High-frequency (6× per week) resistance training does not seem to offer additional strength and hypertrophy benefits over lower frequency (3× per week) when volume and intensity are equated. Coaches and practitioners can therefore expect similar increases in strength and lean body mass with both 3 and 6 weekly sessions.